Accounting Students' Perceptions of the Use of Artificial Intelligence (AI) in Higher Education at Semarang State PolytechnicAccounting Students' Perceptions of the Use of Artificial Intelligence (AI) in Higher Education at Semarang State Polytechnic - Alvianita Gunawan Putri; Ulfah Hidayati; Sri Murtini; Ahmad Wafa Mansur; Noor Ardiansah (Dhana, 2026)
This study aims to explore the perceptions of accounting students at Politeknik Negeri Semarang regarding the use of Artificial Intelligence (AI) in higher education. The rapid development of AI has significantly transformed learning processes, requiring students to integrate technological literacy with accounting competencies. This research employed a quantitative survey method using a structured questionnaire distributed to 39 accounting students. The instrument measured several variables, including the effectiveness of AI use, the effectiveness of chatbot-based learning assistance, students’ AI proficiency, lecturers’ AI competence, and overall student perceptions of AI integration in learning. The data were analyzed using SPSS through descriptive statistics, validity and reliability testing, and factor analysis. The findings indicate that students generally hold positive perceptions toward AI utilization in higher education. They consider AI tools, including chatbots, helpful in supporting learning efficiency, improving understanding, and assisting in completing academic tasks. Students also reported adequate levels of AI proficiency, although improvements in AI-related teaching competence among lecturers are still needed. Overall, the study highlights the importance of strengthening AI literacy in accounting education to enhance students’ readiness for future professional demands